Geochronology and geochemistry of zircon from Early to Middle Devonian granitic and felsic volcanic rocks from the Cashes Ledge igneous suite, central Gulf of Maine, USA - Kuiper, Yvette D.; Barr, Sandra M.; Crowley, James L.; Souders, A. Kate (Atlantic Geoscience, 2023)
New zircon U–Pb, trace element, and Lu–Hf laser ablation inductively coupled mass spectrometry (LA-ICP-MS) data are presented for five Early to Middle Devonian granitic and felsic volcanic rocks from the Cashes Ledge igneous suite, central Gulf of Maine, USA. These samples were previously analyzed by U–Pb LA-ICP-MS and whole-rock geochemical methods and the new data generally corroborate the earlier results. Coarse-grained alkali-feldspar granite from northwest of the Fundy magnetic anomaly, the interpreted fault boundary in the offshore between Gondwanan microcontinents Ganderia to the northwest and Avalonia to the southeast, yielded a crystallization age of 414 ± 2 Ma. Southeast of the inferred fault, crystallization ages are 385 ± 3 Ma and 386 ± 3 Ma for two crystal tuff samples near the fault, 403 ± 3 Ma for an alkali-feldspar granite ~50 km southeast of the fault, and 399 ± 5 Ma for syenogranite ~25 km southeast of the fault, which also yielded inherited grains at ~1.3 Ga and between 613 ± 15 Ma and 558 ± 9 Ma. Lu–Hf LA-ICP-MS data for zircon retaining igneous crystallization ages have εHf(t) between 2.9 and 13.1 and model ages based on felsic sources between 0.52 and 1.04 Ga, reflecting a mix of late Mesoproterozoic (Avalonian?) basement and primitive melt, possibly in an extensional setting. Zircon Nb/Hf ratios generally greater than 0.001 indicate a predominately within-plate/anorogenic/rift setting, consistent with their whole-rock chemistry. U/Yb-Nb/Yb and U/Yb-Hf tectonic setting discrimination diagrams show ocean island to continental arc signatures, with a stronger continental arc signature for the syenogranite. Most zircon grains have Eu/Eu* values less than 0.1, indicating a crustal thickness of ~30 km or less at the time of their crystallization.